Basic education at a distance - Bradley, Jo, 1942-; Yates, Chris, 1953- (World review of distance education and open learning, 2000)
This book assesses the impact and effect of the experience of basic education at a distance all over the world and in a variety of forms. This is the first major overview of this topic for twenty years.